2018
DOI: 10.21276/ijcmr.2018.5.6.29
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Demographic profile in Acute Myocardial Infarction: A Prospective Study from Tertiary Care Rural Hospital in North India

Abstract: Introduction: Atherosclerosis is a multi-factorial disease involving the interplay of genetic and environmental factors. Cardiovascular disease (CVD) is rising in low income countries. Studies conducted to assess the prevalence of cardiovascular risk factors among different regions of the country show variation in different age groups of urban and rural population. Current research aimed to study the conventional risk factors in patients of acute myocardial infarction (AMI) presenting in a rural tertiary care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…A comparative study between the rural and the urban population suffering from cardiovascular diseases in India show that its incidence is more in the urban population than rural by 11%. 5 Even in the month of August 2021, in the times of COVID-19 Pandemic, it was observed that the number of deaths in Pune was more due to Non-communicable disease than from COVID-19. This is indicative of the three fold rise in the incidence of non-communicable diseases in the city.…”
Section: Introductionmentioning
confidence: 99%
“…A comparative study between the rural and the urban population suffering from cardiovascular diseases in India show that its incidence is more in the urban population than rural by 11%. 5 Even in the month of August 2021, in the times of COVID-19 Pandemic, it was observed that the number of deaths in Pune was more due to Non-communicable disease than from COVID-19. This is indicative of the three fold rise in the incidence of non-communicable diseases in the city.…”
Section: Introductionmentioning
confidence: 99%
“…Socioeconomic determinants of health are answerable for determining nearly half of the health of a population, and they also powerfully affect health behaviors, the second greatest contributor to health and permanency [11]. Non-communicable diseases have a multifactorial cause and account for more than fifty percent of the deaths internationally [12]. However, to date, no studies have been conducted on the risk factors of MI in Sulaimani of Iraq; therefore, the current study has intended to assess the common risk factors of a heart attack such as smoking, physical inactivity, hypertension, diabetes mellitus, unhealthy diets, and family history.…”
Section: Introductionmentioning
confidence: 99%
“…(5) As with the western studies, even the Indian studies point that increasing age is a definite risk factor for developing acute coronary syndromes. (6)(7)(8) It may be construed that younger age group may be taken as significant attribute in the low risk ACS group. Similarly because of the inherent protection provided by estrogen to female and the lower incidence of risk factors (smoking, alcoholism, etc), females are generally at low risk in acute coronary syndromes.…”
Section: Introductionmentioning
confidence: 99%